Parametric Appraisal of Process Parameters for Adhesion of Plasma Sprayed Nanostructured YSZ Coatings Using Taguchi Experimental Design - Sisir Mantry; Barada K. Mishra; Madhusudan Chakraborty (The Scientific World Journal)
This paper presents the application of the Taguchi experimental design in developing nanostructured yittria stabilized zirconia (YSZ) coatings by plasma spraying process. This paper depicts dependence of adhesion strength of as-sprayed nanostructured YSZ coatings on various process parameters, and effect of those process parameters on performance output has been studied using Taguchi’s L16 orthogonal array design. Particle velocities prior to impacting the substrate, stand-off-distance, and particle temperature are found to be the most significant parameter affecting the bond strength. To achieve retention of nanostructure, molten state of nanoagglomerates (temperature and velocity) has been monitored using particle diagnostics tool. Maximum adhesion strength of 40.56 MPa has been experimentally found out by selecting optimum levels of selected factors. The enhanced bond strength of nano-YSZ coating may be attributed to higher interfacial toughness due to cracks being interrupted by adherent nanozones.